Analisis Persuasi Assertive dalam Kumpulan Lirik Lagu The Peal - Khaidar Naufal Pasingsingan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the forms of assertive persuasion found in a collection of song lyrics by The Peal by employing a pragmatic approach, specifically Searle’s classification of speech acts. The focus of the research is to examine how the lyrics represent assertive functions as a means of conveying messages, attitudes, and perspectives intended by the songwriter. This study uses a descriptive qualitative method involving several stages: listening closely to the lyrics, identifying linguistic indicators of assertive persuasion, and explaining the meanings and communicative functions embedded in the utterances.The findings reveal that six selected songs by The Peal contain various forms of assertive persuasion. The song Isak Tangis demonstrates an assertive act of warning, while Berbahagialah reflects an act of suggesting. The song Porak Poranda represents the act of complaining, whereas Kehancuran shows elements of asserting or criticizing. The song Cinta Mana yang Kau Bela? contains elements of boasting, and Belum Waktunya reflects the act of reporting or presenting information. These results indicate that The Peal’s song lyrics function not only as artistic expressions but also as persuasive communicative media that convey social and emotional messages through diverse assertive speech acts.